Formulation and Evaluation of Avocado Leaf Extract Cream Preparation (Persea americana Mill.) - Sitanggang, Titin Krisdayanti; Yunus, Muhammad; Ginting, Astriani Natalia Br (PCJN: Pharmaceutical and Clinical Journal of Nusantara, 2025)
As the outermost organ of the body, the skin is vulnerable to disorders such as inflammation, infection, and irritation, necessitating the use of effective and safe topical preparations. Avocado leaves (Persea americana Mill.) contain bioactive compounds such as flavonoids and polyphenols with known antioxidant and anti-inflammatory properties. This study aimed to formulate and evaluate a cream preparation containing ethanolic extract of avocado leaves as a natural active ingredient. The extract was obtained by maceration using 96% ethanol and formulated into three concentrations: 10% (F1), 15% (F2), and 20% (F3). Evaluations included organoleptic properties, homogeneity, pH, spreadability, and physical stability. The results showed that all formulations had a homogeneous appearance, characteristic color according to extract concentration, were odorless and tasteless. The pH values ranged within a safe range for skin application (4.83–4.90), and the best spreadability was observed in formulation F2. Increasing extract concentration tended to decrease spreadability due to increased viscosity. All formulations demonstrated good physical stability during cyclic stability testing. Based on these findings, it can be concluded that avocado leaf ethanolic extract can be effectively formulated into a stable, safe, and physically acceptable cream suitable for topical use.